The control of mimicry by social signals - Wang, Yin (2012)
One remarkable feature of social interactions is spontaneous mimicry. People have a tendency to unconsciously imitate other’s behaviours. This mimicry increases liking and affiliation between individuals and plays an important role in social cognition. Though mimicry is not normally consciously controlled, past research suggests that people mimic differently across social situations. In order to better understand the flexibility of mimicry in socal contexts, this thesis examined how social signals impact on mimicry by using a cognitive approach. Four behavioural studies consistently suggest that mimicry is subtly and strategically controlled by social signals. Specifically, in the first study we found that eye gaze is a powerful controlling signal on mimicry. Direct gaze rapidly and specifically enhances mimicry of intransitive hand movements. In the second study, we clarified that this eye contact effect on mimicry is not due to any arousal or attentional effect, but is driven by the social cue of direct gaze. In the third study, we found a joint effect of likeability and social status on mimicry. These two features interact in driving mimicry and optimize the affiliative function of mimicry in social interaction. Finally in the fourth study, we found that mimicry is sensitive to social primes. Prosocial and antisocial primes subtly modulate mimicry according to the self-relatedness of the primes. To further investigate the neural mechanism of the sutble control of mimicry by social signals, functional magnetic resonance imaging was used to examine the effect of eye contact on mimicry. The results showed that two key brain systems for social cognition—medial prefrontal cortex (mPFC) and mirror neuron system (MNS)—work together to control mimicry on line in social contexts. In particular, dynamic causal modelling analysis revealed that mPFC is the originator of the eye contact effect on mimicry and this region modulates the sensory inputs to the MNS according to gaze directions. These findings suggest that mPFC plays a key role in the strategic control of mimicry in social contexts. All experiments are then discussed in relation to current theories of mimicry. We suggest that this subtle and strategic control of mimicry is essential to human competence in social interactions and is important for our understanding of why and how people mimic.